Cultura e identidade em São Paulo: a imigração síria e libanesa - Marcia Maria Cabreira (EccoS – Revista Científica)
The article focuses Syrian and Lebanese immigration in São Paulo, between 1870 and 1940, trying to elucidate which symbols of those ethnic group are still present in paulistana (from São Paulo city) and Brazilian societies. As theoretical fundament for this study we use the definition of landscape, connect to memory and place, using contributions of scholars like Sauer, Berque, Sénecal and Bailly.